2006
DOI: 10.1002/mop.21379
|View full text |Cite
|
Sign up to set email alerts
|

A folded and bent internal loop antenna for GSM/DCS/PCS operation of mobile handset applications

Abstract: A novel dual band-notched monopole ultra-wideband antenna is proposed, in which the parasitic strip creates one band-notch at 5.5 GHz and the tuning stub produces another band-notch at 3.5 GHz.The experimental results show that the proposed antenna, with a compact size of 20 ϫ 31.5 mm 2 , has a bandwidth of 3. 1-10.6 GHz with voltage standing wave ratio (VSWR) less than 2, except the bandwidths of 3. INTRODUCTIONWith the development of modern wireless and mobile communication, the ultra-wideband systems h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…In the recent studies [1][2][3][4][5][6][7], the loop antennas have been shown to be promising candidates for application in the mobile phone as internal multiband antennas with reasonable occupied size. These multiband loop antennas are generally achieved by printing the desired loop metal pattern on the system circuit board or thin dielectric substrate [1][2][3], forming the loop metal pattern on the surfaces of the chip base as surface-mount elements [4], or mounting the loop metal strip above the system ground plane of the mobile phone [5][6][7]. For these reported loop antennas, however, they are mainly operated at their 0.5-wavelength resonant mode to form the antenna's lower band to cover GSM (890 -960 MHz) operation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent studies [1][2][3][4][5][6][7], the loop antennas have been shown to be promising candidates for application in the mobile phone as internal multiband antennas with reasonable occupied size. These multiband loop antennas are generally achieved by printing the desired loop metal pattern on the system circuit board or thin dielectric substrate [1][2][3], forming the loop metal pattern on the surfaces of the chip base as surface-mount elements [4], or mounting the loop metal strip above the system ground plane of the mobile phone [5][6][7]. For these reported loop antennas, however, they are mainly operated at their 0.5-wavelength resonant mode to form the antenna's lower band to cover GSM (890 -960 MHz) operation.…”
Section: Introductionmentioning
confidence: 99%
“…The limitation can be overcome by linearization techniques. A number of linearization methods have been reported to reduce nonlinear distortion products of a direct-modulated LD [3][4][5][6]. The optical feed-forward technique provides better linearity and wider bandwidth than the other techniques as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other applications could include indoor WLAN antennas for mounting on ceilings or other horizontal surfaces. Recently, a variety of multiband loop antennas for wireless wide area network (WWAN) operation in the mobile phone have been demonstrated [1][2][3][4][5][6][7]. These loop antennas are attractive for mobile phone applications in part, because their excited surface current paths are in a closed form, which is different from the conventional mobile phone antennas such as the monopoles or planar inverted-F antennas (PIFAs), whose excited surface current paths are in an open form [8].…”
mentioning
confidence: 99%
“…In this case, the variations in the dimensions of the system ground plane will show smaller effects on the performances of the loop antenna. For the reported multiband loop antennas for mobile phone applications [1][2][3][4][5][6][7], most of them use a direct feed, and the obtained operating bands cover several of the GSM850 (824 -894 MHz), GSM900 (890 -960 MHz), GSM1800 (1710 -1880 MHz), GSM1900 (1850 -1990, and UMTS (1920( -2170 bands for WWAN operation. In this article, we present a surfacemount loop antenna with a capacitively coupled feed for achieving seven-band operation covering all the five operating bands for WWAN operation, the 2.4-GHz band (2400 -2484 MHz) for wireless local area network (WLAN) operation, and the 2.5-GHz band (2500 -2690 MHz) for worldwide interoperability for microwave access (WiMAX) operation [9 -15].…”
mentioning
confidence: 99%